Growth mechanisms of co‐evaporated kesterite: a comparison of Cu‐rich and Zn‐rich composition paths. (24th January 2013) - Hsu, Wan‐Ching; Repins, Ingrid; Beall, Carolyn; DeHart, Clay; To, Bobby; Yang, Wenbing; Yang, Yang; Noufi, Rommel
ABSTRACT Earth abundant kesterite solar cells have achieved 7–10% cell efficiency mostly by processes that separate the film deposition and the annealing into two sequential steps. In contrast, co‐evaporation onto a high‐temperature substrate, demonstrating previous success in chalcopyrite (Cu(In, Ga)Se2) solar cells, allows real‐time composition control. Chalcopyrite research widely supports the model that Cu‐rich growth conditions assist grain growth, and subsequently, the endpoint composition can be adjusted back to Cu‐poor via monitoring the surface emissivity of the film. On the basis of the same intentions, the recent development of co‐evaporated kesterite (Cu2ZnSnSe4) adapts the concept and achieves 9.2% efficiency. To understand the effect of growth strategies, this study examines the phase evolution, grain morphology, and device performance in Cu‐rich growth and other strategies (Zn‐rich and close‐to‐stoichiometric). By characterizing films obtained from interrupted depositions and also interpreting the variation in surface emission during growths, this study found a subtle hindrance in the reaction of CuxSey and ZnSe possibly caused by the volatile nature of SnSex. The hindrance explains why, distinctive from chalcopyrite, little difference in grain size is observed between kesterite films made by Cu‐rich versus Zn‐rich growth at these deposition rates. At last, a Zn‐rich growth 9.1% device, certified by the National Renewable Energy Laboratory, is presented, which equals the performance of the previously‐reported Cu‐rich growth device. At the present stage, we believe the Cu‐rich and Zn‐rich growth share equal promise for the optimization of kesterite solar cells. Copyright © 2013 John Wiley & Sons, Ltd.